2015
DOI: 10.1111/psyp.12437
|View full text |Cite
|
Sign up to set email alerts
|

How inappropriate high‐pass filters can produce artifactual effects and incorrect conclusions in ERP studies of language and cognition

Abstract: Although it is widely known that high-pass filters can reduce the amplitude of slow ERP components, these filters can also introduce artifactual peaks that lead to incorrect conclusions. To demonstrate this and provide evidence about optimal filter settings, we recorded ERPs in a typical language processing paradigm involving syntactic and semantic violations. Unfiltered results showed standard N400 and P600 effects in the semantic and syntactic violation conditions, respectively. However, high-pass filters wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
227
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(231 citation statements)
references
References 46 publications
4
227
0
Order By: Relevance
“…They were re-referenced to the average of the left and right mastoids and filtered using a 0.1 -40 Hz band-pass filter offline. This highpass filter value was tested in a recent study and found to not introduce artefactual effects (Tanner, Morgan-Short, & Luck, 2015). A 15Hz low-pass filter was applied for the presentation of grand averages only, but was not used in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…They were re-referenced to the average of the left and right mastoids and filtered using a 0.1 -40 Hz band-pass filter offline. This highpass filter value was tested in a recent study and found to not introduce artefactual effects (Tanner, Morgan-Short, & Luck, 2015). A 15Hz low-pass filter was applied for the presentation of grand averages only, but was not used in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…replicating the strong and statistically significant effect of cloze on noun-N400s 4,6 . The effect yielded strong to extremely strong evidence for the null hypothesis, whereas our noun data 103 yielded extremely strong evidence for the alternative hypothesis (upper graphs).…”
mentioning
confidence: 99%
“…Current theories of language comprehension [1][2][3] posit prediction, or 3 context-based pre-activation, as an essential mechanism occurring at all levels of linguistic 4 representation (semantic, morpho-syntactic and phonological/orthographic) and facilitating 5 the integration of words into the unfolding discourse representation. The strongest evidence 6 to date for phonological pre-activation comes from DeLong, Urbach and Kutas 4 , who 7 monitored participants' electrophysiological brain responses as they read sentences, presented 8 one word at a time, with expected/unexpected indefinite article + noun combinations like,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, baseline correction has been studied in the context of EEG/ MEG data, as shown by a recent debate about whether or not baseline correction of EEG/ MEG data should be abandoned in favor of high-pass filtering (Maess, Schröger, & Widmann, 2016;Tanner, Morgan-Short, & Luck, 2015;Tanner, Norton, Morgan-Short, & Luck, 2016). However, pupil-size data is different from EEG/ MEG data.…”
Section: Of 25mentioning
confidence: 99%